2013
DOI: 10.1007/s00018-013-1512-0
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional networks regulating the costamere, sarcomere, and other cytoskeletal structures in striated muscle

Abstract: Structural abnormalities in striated muscle have been observed in numerous transcription factor gain- and loss-of-function phenotypes in animal and cell culture model systems, indicating that transcription is important in regulating the cytoarchitecture. While most characterized cytoarchitectural defects are largely indistinguishable by histological and ultrastructural criteria, analysis of dysregulated gene expression in each mutant phenotype has yielded valuable information regarding specific structural gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 114 publications
(139 reference statements)
1
27
0
1
Order By: Relevance
“…MEF2A was predicted to regulate genes involved in actin cytoskeletal rearrangement, consistent with its regulation of structural genes encoding proteins localized to the costamere in cardiac muscle (15,46). It is intriguing that regulation of the actin cytoskeleton was not identified among the top canonical pathways in the MEF2B, -C, or -D dysregulated gene sets, considering these MEF2 proteins have been shown to regulate muscle structural genes in vitro and in vivo (46). Although expression profiling clearly identified this category of genes in all of the MEF2 knockdowns, other pathways were found to be more significantly dysregulated in the MEF2B, -C, or -D gene sets.…”
Section: Discussionmentioning
confidence: 76%
“…MEF2A was predicted to regulate genes involved in actin cytoskeletal rearrangement, consistent with its regulation of structural genes encoding proteins localized to the costamere in cardiac muscle (15,46). It is intriguing that regulation of the actin cytoskeleton was not identified among the top canonical pathways in the MEF2B, -C, or -D dysregulated gene sets, considering these MEF2 proteins have been shown to regulate muscle structural genes in vitro and in vivo (46). Although expression profiling clearly identified this category of genes in all of the MEF2 knockdowns, other pathways were found to be more significantly dysregulated in the MEF2B, -C, or -D gene sets.…”
Section: Discussionmentioning
confidence: 76%
“…On the basis of the established role of MEF2 in regulating the muscle cytoarchitecture, we were interested in determining whether the expression of sarcomere genes is dependent on these Gtl2-Dio3 miRNAs (18). As expected, acute knockdown of MEF2A in NRVMs resulted in significant down-regulation of sarcomere genes (Fig.…”
Section: Mir-410 and Mir-495 Are Expressed In The Heart And Downregulmentioning
confidence: 80%
“…Previous studies from our laboratory demonstrated that MEF2A (myocyte enhancer factor 2A), but not the related family members MEF2C and MEF2D, regulates the integrity of costameres, specialized focal adhesions in muscle (11,12). Because costamere structure was not significantly affected by MEF2C or MEF2D deficiency, we were interested in determining the processes dependent on these MEF2 protein isoforms in cardiomyocytes.…”
mentioning
confidence: 99%